2020
DOI: 10.1037/men0000254
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of subjective masculine norms in the United States.

Abstract: What are men's perceptions of the most important masculine norms in the United States? And how are their endorsement of these norms associated with their well-being and gender-related outcomes (e.g., sexism)? Guided by the subjective gender norms model (Wong, Ringo Ho, Wang, & Fisher, 2016), this study investigated 463 U.S. men's (M age ϭ 35.14) subjective masculine norms, defined as perceptions of the most important masculine norms in a group or society. The authors had two goals: (a) identify the most preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Concurrently, social constructionism asserts that masculinities do not contain universal and invariant meanings. Instead, there are multiple, dynamic meanings associated with men that reflect a society’s culture and individual constructions of masculinities (Addis et al, 2016; Wong et al, 2020). Hence, masculine norms that encourage men’s domination over women, while difficult to eradicate, are neither natural nor inevitable.…”
Section: Defining Masculinitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Concurrently, social constructionism asserts that masculinities do not contain universal and invariant meanings. Instead, there are multiple, dynamic meanings associated with men that reflect a society’s culture and individual constructions of masculinities (Addis et al, 2016; Wong et al, 2020). Hence, masculine norms that encourage men’s domination over women, while difficult to eradicate, are neither natural nor inevitable.…”
Section: Defining Masculinitiesmentioning
confidence: 99%
“…Related to masculinity ideologies, the social norms approach (Wong et al, 2020; Zou & Leung, 2015), highlights the role that perceived masculine norms play in regulating attitudes and behavior. For instance, men’s overestimation of their counterparts’ approval of and degree of aggression might motivate them to enhance their aggressiveness to conform to perceived norms (Vandello et al, 2009).…”
Section: Domain 2: Other-ascribed Masculinitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical aggression is deemed in most cases to be an overreaction and immoral in modern society and, while people higher in masculine honor beliefs are more permissive of aggression, there are limits to their endorsements (see O’Dea et al, 2019; O’Dea et al, Under review). In fact, Wong et al (2020) showed that when asked about prescriptive and proscriptive norms of masculinity, one of the most widely prescribed and proscribed behaviors was nonaggression (e.g., “Should not act out violently against anyone”; p. 551). However, these anti-aggression societal norms are often studied in the context of general everyday behavior in which case, arguably, most people would be against the exhibition of violence—so the question of when violence is permissible, or perceived as permissible, arises.…”
Section: Bottom-up Influences On Aggressionmentioning
confidence: 99%
“…On the other hand, this also highlights that men with higher BSRI-M may strive more for status while also being more sensitive to its loss. This is supported by work showing that men's endorsement of strict masculinity norms is associated with greater sensitivity to threats regarding their masculine identity (Bock & Brown, 2021;Wong et al, 2020). Neither endorsement of traditional masculinity nor gender role conflict emerged as significant moderators influencing the association between loss of social status due to the COVID-19 pandemic and past-month suicide attempt.…”
Section: Integration Of Findingsmentioning
confidence: 92%